Combined Transfer of the Gluteus Maximus and Tensor Fasciae Latae for Irreparable Gluteus Medius Tear Using Contemporary Techniques: Short-Term Outcomes. Issue 4 (October 2020) - Maldonado, David R.; Annin, Shawn; Chen, Jeffrey W.; Yelton, Mitchell J.; Shapira, Jacob; Rosinsky, Philip J.; Lall, Ajay C.; Domb, Benjamin G.
Abstract : Background: Combined transfer of the gluteus maximus and tensor fasciae latae (TFL) has been acknowledged as a treatment for irreparable full-thickness gluteus medius tears; yet, there is a paucity of reports on outcomes for this topic in the current literature. The purpose of the present study was to report short-term patient-reported outcome scores in patients who underwent combined transfer of the gluteus maximus and TFL in the setting of an irreparable gluteus medius tear. Methods: Data for patients who underwent hip preservation and hip arthroplasty between July 2011 and November 2017 were prospectively collected and retrospectively reviewed. Patients were considered for this study if they had undergone combined transfer of the gluteus maximus and TFL for irreparable gluteus medius tears. Inclusion criteria consisted of patients who had a minimum 1-year follow-up for the modified Harris hip score, Non-Arthritic Hip Score, Hip Outcome Score Sports Specific Subscale, visual analog scale score for pain, and patient satisfaction. The exclusion criterion was Workers' Compensation status. Results: The study included 18 hips in 18 patients who underwent combined transfer of the gluteus maximus and TFL, with a mean follow-up of 39.75 months (range, 12.04 to 93.88 months). The average age was 68.48 ± 11.05 years, the average body mass index was 29.54 ± 6.23 kg/m 2, and 13 patients were female. Abductor strength improved in 7 of 17 patients, with abduction data unavailable for 1 patient. Significant improvements were observed in modified Harris hip score from 49.73 ± 16.85 to 74.94 ± 17.91 (p < 0.001), Non-Arthritic Hip Score from 55.02 ± 22.53 to 72.78 ± 19.17 (p = 0.032), and visual analog scale for pain from 5.42 ± 3.42 to 1.57 ± 1.68 (p = 0.0004). No secondary surgeries were reported. Conclusions: Significant improvements in patient-reported outcomes were observed in patients who underwent combined transfer of the gluteus maximus and TFL for the treatment of irreparable full-thickness gluteus medius tears at short-term follow-up. Level of Evidence: Level IV . See Instructions for Authors for a complete description of levels of evidence.